Manajemen Laba, Profitabilitas dan Kepemilikan Keluarga dan Tax Avoidance - Maitriyadewi, Ni Luh Ratna Pradnya; Noviari, Naniek (E-Jurnal Akuntansi; Vol 30 No 6 (2020)DO - 10.24843/EJA.2020.v30.i06.p04, 2020)
One of the biggest sources of income for the country is tax. Taxes are used to finance the national development of a country. The results of Indonesia's tax revenue have fluctuated from 2016 to 2018. Tax revenue is fluctuating because of less optimal tax collection or the presence of tax avoidance from taxpayers. The purpose of this study is to obtain empirical evidence regarding the effect of earnings management, profitability, and family ownership on tax avoidance. This research was conducted by taking the population of consumer goods companies listed on the Stock Exchange in 2016-2018. Through the purposive sampling method in accordance with predetermined criteria, researchers obtained 27 sample companies. The data analysis technique used is multiple linear regression analysis. The results obtained are earnings management and profitability variables have a positive effect on tax avoidance. While the family ownership variable has no effect on tax avoidance. Keywords: Earning Management; Profitability; Family Ownership; Tax Avoidance.